Brivaracetam as adjunctive treatment for uncontrolled partial epilepsy in adults: A phase III randomized, double‐blind, placebo‐controlled trial - Victor Biton; Samuel F. Berkovic; Bassel Abou‐Khalil; Michael R. Sperling; Martin Johnson; Sarah Lu (2013)
Summary Purpose Brivaracetam ( BRV ) is a novel high‐affinity synaptic vesicle protein 2A ligand currently being investigated for the treatment of epilepsy. The purpose of this phase III study was to evaluate the efficacy and safety/tolerability of adjunctive BRV in adults with uncontrolled partial‐onset (focal) seizures. Methods This was a prospective, multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group, fixed‐dose trial (N01253; NCT00464269). Adults aged 16–70 years with well‐characterized partial epilepsy not fully controlled despite treatment with one or two antiepileptic drugs ( AED s) were enrolled. Patients who experienced eight or more partial‐onset seizures, whether or not secondarily generalized, during the 8‐week prospective baseline period were randomized (1:1:1:1) to receive twice‐daily placebo ( PBO ) or BRV (5, 20, or 50 mg/day) without titration. The primary efficacy endpoint was percent reduction over PBO in baseline‐adjusted partial‐onset seizure frequency/week during the 12‐week treatment period. Comparison of BRV with PBO was sequential (50, 20 mg/day, then 5 mg/day). Secondary endpoints included ≥50% responder rate and median percent reduction from baseline in partial‐onset seizure frequency/week. Post hoc analyses included the primary efficacy endpoint evaluated over 28 days and exploratory subanalyses of efficacy by seizure subtype. Safety and tolerability assessments included treatment‐emergent adverse events ( TEAE s), laboratory tests, electrocardiography, vital signs, and physical and neurologic examinations. Key Findings Of 400 patients randomized, 396 were included in the intent‐to‐treat ( ITT ) population ( PBO n = 98, BRV 5 mg/day n = 97, BRV 20 mg/day n = 100, BRV 50 mg/day n = 101) and 392 comprised the modified ITT ( mITT ) population. A total of 361 (91.2%) of 396 patients completed the study. Most patients (78.3%) were receiving two concomitant AED s. Percent reduction in partial‐onset seizure frequency/week over PBO was −0.9% (p = 0.885) for BRV 5 mg/day, 4.1% (p = 0.492) for BRV 20 mg/day, and 12.8% (p = 0.025) for BRV 50 mg/day ( mITT population). Statistical significance was also achieved for the percent reduction over PBO in baseline‐adjusted partial‐onset seizure frequency/28 days for BRV 50 mg/day (22.0%; p = 0.004) but not for the other BRV dose groups. In the BRV 50 mg/day group, statistical significance was also seen for the ≥50% responder rate ( BRV 32.7% vs. PBO 16.7%; p = 0.008) and median percent reduction from baseline in partial‐onset seizure frequency/week ( BRV 30.5% vs. PBO 17.8%; p = 0.003). In the exploratory subanalysis by seizure subtype, median percent reduction from baseline in seizure frequency/week and ≥50% responder rate were numerically greater than PBO in the BRV 20 and 50 mg/day groups for simple partial, complex partial, and secondarily generalized seizures. BRV was generally well tolerated, with the majority of TEAEs being mild‐to‐moderate in intensity. Of the TEAEs reported by ≥5% patients, those with a frequency >3% higher than PBO for any dose of BRV compared with PBO were somnolence, dizziness, fatigue, influenza, insomnia, nasopharyngitis, vomiting, diarrhea, urinary tract infection, and nausea. Significance Adjunctive BRV at a daily dose of 50 mg was associated with statistically significant reductions in seizure frequency compared with PBO . All doses of BRV showed good tolerability throughout the study.